First Database Report on Cardiothoracic Surgery in Tehran Heart Center - AA Karimi; SH Ahmadi; S Davoodi; M Marzban; N Movahedi; K Abbasi; A Salehi Omran; M Shirzad; S Sadeghian; SH Abbasi; M Lotfi-Tokaldany; M Soleymanzadeh; et al. (Tehran University of Medical Sciences, 2008)
Background: The use of cardiac surgical database is necessary for evaluating and improving the quality of care. The aim of this report was to provide useful information for surgeons in Iran and other countries for their daily practice. Methods: We analyzed data from 14288 consecutive patients in four different types of procedures, namely isolated coronary artery bypass grafting (CABG), combined CABG and valve (CABG-V), only valve (V), and other adult cardiac surgical operations from 2002 to 2006. Results: The activity load increased from 1765 in 2002 to 3309 surgical operations in 2006 with almost 87.2% of activity being isolated CABG. The mortality rate for CABG was 1%, which decreased from 1.7% to 0.9% over the five years. The mortality rates for CABG-V and V were 5.8% and 4.8% in the last year of the study, respectively. Over the 5 yr period, the proportion of urgent operations increased substantially from 4% to 24.5% (P< 0.0001), causing a reduction in elective operations. The mean length of hospital stay for the entire population was 8.38±5.74 d, which remained almost steady during the study period. Conclusion: This database can serve as a valuable resource of preoperative measurers and surgical outcomes for surgeons and researchers with a view to improving overall surgical performance.